Diseño de la planificación estratégica situacional de la empresa Macropack Cía. Ltda. productora de cartón para exportación de flores ubicada en la ciudad de Quito. - Ortiz Vaca, Sthefany Virginia (2014)
Macropack Limited Company since its foundation in 2009hasa continuous growth, covering much of the floriculture market thanks to their negotiation power, as a result has achieved an exclusive customers base, considered the strongest in the flower industry, because there is great demand of microcorrugated sheets of cardboard and separator especially in high seas on flower exports, so the company needs to increase its production volumes and sales, for this the Company needs important economic resources such as industry needs high investment and availability of working capital, which currently does not possess. This work is based on the overall study of the Macropack Limited Company, where was observed positive and negative aspects involving the company, for that reason to propose the design of a strategic planning to help the company to project into the future, with the goal of improving its position of the floriculture market, through the creation strategies to add value to its brand and be more competitive.